Detection of veterinary antibiotic residues in fresh fecal samples collected from selected pig farms in the City of Baybay, Leyte, Philippines - Ymas, Bianca Therese P.; Peña Jr, Santiago T. (Annals of Tropical Research, 2023)
Investigations on the presence of antibiotic residues in livestock manure are becoming an integral part on the quest against antimicrobial resistance (AMR). Moreover, as a potential hazard to human health and the environment, the threat of antibiotic residues cannot be taken lightly. As one of the biggest pig producers in Eastern Visayas, the Province of Leyte, Philippines is presented with the challenge to sustain the pork requirements of the region despite its limited overall production. This study aims to determine the prevalence of antibiotic residues present in the swine manure among selected commercial piggery farms in Baybay City, Leyte. Using 147 fecal samples collected from different classes of pigs and following standard microbial inhibition plate technique, this study consistently found inhibitory action against the growth of Bacillus subtilis across three pH levels from fecal samples collected from grower-finishers, and breeders unlike samples collected from both the lactating and farrowing sows. These results may provide insights and baseline information useful for similar studies on antibiotic residues in meat and meat products that may have implications on human health.